The in-session discourse of unresolved/disorganized psychotherapy patients: An exploratory study of an attachment classification - Talia, Alessandro; Taubner, Svenja; Miller-Bottome, Madeleine; Muurholm, Signe Dall; Winther, Anna; Frandsen, Frederik Weischer; Harpøth, Tine; Onofri, Antonio; Kongerslev, Mickey T.; Simonsen, Sebastian; Poulsen, Stig; Duschinsky, Robbie (Frontiers in Psychology, 2022)
The concept of Unresolved/disorganised attachment (U/d) has generated considerable interest among clinicians. This is in part based on its empirical associations with adult mental health, parenting practices, and treatment outcomes. Despite decades of theorising, however, we have little empirical information regarding how patients with a U/d classification assigned by accredited coders actually behave or speak in psychotherapy sessions. Here, we take a step in bridging this gap by reporting on a qualitative analysis describing the psychotherapy session transcripts of 40 outpatients who were independently found to be U/d on the Adult Attachment Interview (AAI), the gold standard measure of adult attachment research. These patients were compared to others without a U/d classification from a larger sample of 181. In this paper, we discuss two different discourse styles associated with a U/d classification. Some of these patients seemed to make no effort to elicit the therapist’s endorsement of what they said, for example they did not motivate their statements sufficiently, or did not consider others’ intentions or experiences. Other of these patients were credible, but left the listener uncertain about what was the point of their discourse, for example because they strikingly omitted to discuss the consequences of their experiences, or interrupted their narratives mid-way. In the discussion, we put these observations in relation with recent thinking on attachment and epistemic trust, and we discuss how this qualitative study may form the basis for future quantitative studies of psychotherapy.